Acute Muscle Trauma due to Overexercise in an Otherwise Healthy Patient with Cystic Fibrosis. (23rd January 2012) - Neubauer, Henning; Wirth, Clemens; Ruf, Katharina; Hebestreit, Helge; Beer, Meinrad
Abstract : Cystic fibrosis (CF) is one of the most common inherited diseases and is caused by mutations in the CFTR gene. Although the pulmonary and gastrointestinal manifestations of the disease remain in the focus of treatment, recent studies have shown expression of the CFTR gene product in skeletal muscle cells and observed altered intramuscular Ca 2+ release dynamics in CFTR-deficient animal models. Physical exercise is beneficial for maintaining fitness and well-being in CF patients and constitutes one aspect of modern multimodal treatment, which has considerably increased life span and reduced morbidity. We report on a case of acute muscle trauma resulting from excessive dumbbell exercise in a young adult with cystic fibrosis and describe clinical, laboratory and imaging characteristics of acute exercise-induced muscle injury.